RELEVANSI TUJUAN PENDIDIKAN ISLAM DALAM DIMENSI MODERNITAS - Sumaryati, Sumaryati (AS-SALAM, 2013)
Islamic education is a effort to change behavior of the students in their life,Â  living society, and toward nature around them with the way of education and teaching and along with the good mother of moral which bases on the values of Islam. As a aim of education in Islam which is for making moslem human be healthy and strong body along with having excellent skills, making a good morality, developing the perspicacity, making personality be the whole of soul, body, and mind.The relevance in the contex of now about the purpose of Islamic education, comes from developing potention of innate taught which based on good morality, that afterwards makes related to the cultural and societal values agree with the environment. This conception aims to create the generation characterizes Qurâani in the dimension of modernity that based on technology and science.Keyword: Tujuan Pendidikan Islam, Modernitas